2022
DOI: 10.4142/jvs.21209
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii in cats in mainland China 2016–2020: a meta-analysis

Abstract: Background Toxoplasma gondii can infect humans and most animals and has a very high infection rate worldwide, including in China. The number of people infected with T. gondii in China increases with the number of cats. Objectives We investigated the seropositive rate of T. gondii in cats over the last five years and analyzed the risk factors via meta-analysis. Methods We ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In our study, T. gondii infection rates in cats were similar to IgG seroprevalence of T. gondii infection in Chinese blood donors in China, which suggested that humans should be advised to take control measures to minimize human-dog/cat contact, thereby reducing exposure to T. gondii ( 43 ). The prevalence of T. gondii infection in the samples from dogs and cats in the eastern part of China used in this study was lower than that reported for the western part of the country, which might be related to the level of economic development and hygiene conditions ( 44 ). The DNA positivity rate for dogs and cats was 5.71% in Shanghai in 2012 ( 45 ).…”
Section: Discussioncontrasting
confidence: 66%
“…In our study, T. gondii infection rates in cats were similar to IgG seroprevalence of T. gondii infection in Chinese blood donors in China, which suggested that humans should be advised to take control measures to minimize human-dog/cat contact, thereby reducing exposure to T. gondii ( 43 ). The prevalence of T. gondii infection in the samples from dogs and cats in the eastern part of China used in this study was lower than that reported for the western part of the country, which might be related to the level of economic development and hygiene conditions ( 44 ). The DNA positivity rate for dogs and cats was 5.71% in Shanghai in 2012 ( 45 ).…”
Section: Discussioncontrasting
confidence: 66%
“…A number of studies conducted on toxoplasmosis in the cat population across the globe using diverse serological techniques found that T. gondii is distributed globally [ 21 , 32 , 33 ]. Seroprevalence in cats has been found in many studies in different countries of the world from 2010 to 2020 including those conducted in the USA (19.0%), Brazil (28.6%), Iran (44.6%), Japan (10.9%), and Korea (17.4%) [ 21 , 34 ]. In China, although cats from some provinces were infected by T. gondii with infection rates from 2.5% to 60.0% and an overall infection rate of 20.2% in China before 2020, there have been no epidemiological studies on T. gondii infections in cats in the district of Qinghai, in the QTPA.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that seroepidemiological studies are useful for indicating infection in an area and a special population of cats, which can be used to assess the infection risk for the definitive and intermediate hosts ( 15 ). In recent years, seroprevalence of Toxoplasma in cats has been reported to distribute in 5 to 40% in mainland China, yet seroprevalence can be as high as 100% due to sample size and geography ( 16 , 17 ). Molecular diagnostics of toxoplasmosis were generally based on detection of specific DNA sequences, and the detection of T. gondii DNA in cat feces was generally considered as the presence of oocysts.…”
Section: Introductionmentioning
confidence: 99%